Developing Flipbook-Based Digital Learning Module for University Learners - Fatonah, Umi; Safitri, Ani; Maimunah; Septiani, Mita; Sharikha, Aktsa (JTP - Jurnal Teknologi Pendidikan, 2025)
The development of digital learning tools has progressed educational practices even though there is a need for engaging and validated resources tailored for university-level instruction. There are many digital modules lack rigorous development and validation, potentially limiting their effectiveness in enhancing learning experiences. This Research and Development (R&D) study aimed to develop a digital learning module in a flipbook format specifically designed for university learners. Utilizing the instructional development model procedure, the research employed both qualitative and quantitative methodologies where qualitative data were gathered through expert validation feedback, while quantitative data were collected via expert validation through questionnaires. This research employed data collection instruments included questionnaires, observation, and interviews. The participants of the study included students from educational study program. The developed digital flipbook module underwent rigorous validation by subject matter, media, and language experts, achieving high validity scores of 100%, 89.13%, and 97.22%, respectively. Furthermore, the module was tested with university learners through individual trials (96.875% validity), small group trials (91.67% validity), and field trials (90.21% validity), all indicating a "very valid" rating for all matters. The consistently high validation scores across expert review and learner trials provide valid evidence that the developed digital flipbook module is a suitable and effective media for enhancing the university learners’ learning experience. In conclusion, the findings support the idea that digital flipbook module offer both engaging and validated learning resources for university- level education.